Godamwale Private Company - Shaikh, Ameena (ATLAS SkillTech University, 2024)
This report covers my internship experience at Godamwale Company, a part of my MBA studies. My time at Godamwale Company offered me a diverse range of leaming experiences, each contributing uniquely to my professional development. During my internship at Godamwale Company, I had the opportunity to gain valuable insights and hands-on experience in various aspects of the company's operations. Over the course of my internship, I was involved in several key responsibilities and tasks that enhanced my skills and understanding of the company's operations and financial management. Learnt Preparation of MIS Data with pivot table: Monthly Client Data Auditing: Warehouse Expenses. Direct and Indirect Expenses: List of (Board Resolution & Annual General Meeting) company documents: Managing Diary Filling; Client Ledger Comparison; Reporting for Incomplete Invoice. The most significant takeaway from my internship at Godamwale Company is adaptability. Working in a dynamie environment with diverse individuals has taught me the importance of tailoring my approach to different personalities and situations, enhancing my ability to navigate professional challenges effectively. As the importance of dylari a result, I joined the organization as a fresher, and my experience has not only boosted my confidence in working for any organization but has also significantly improved my skill set in finance and accounting. These enhanced skills will enable me to assist any company in better understanding their profit and loss dynamics.
Project Report on Godamwale Private Company (2022-24) Under the Guidance of Prof. Nikita Nadkarni
Keywords: Logistics